An Islamic Perspective of the Challenges of Older Age in Nigeria - Yahya, Shaykh Ahmad; Abdulhameed Badmas Yusuf (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Late childhood is accompanied by multifaceted problems in Nigeria. Hence, the challenges cut across all facets of life including spiritual, social and economic aspects. This paper therefore addresses these challenges using the provisions of Islam on the care for aged as a recipe for a way out. It assesses these challenges with the theoretical explanation of the duties of individuals and society to the aged. The paper advocates compliance with the dos and don’ts of Islam as regards the rights of the elderly and recommends the dire need for Nigerian government to introduce policies that would enhance social support to the elderly.